ﻣﻜﻮﻧﺎت ﻣﺎ وراء اﻟﺬاﻛﺮة وﻋﻼﻗﺘﮭﺎ ﺑﺈﺳﺘﺮاﺗﯿﺠﯿﺎت اﻟﺘﺬﻛﺮ ﻋﻨﺪ اﻟﻄﻠﺒﺔ ﻓﻲ ﻣﺪارس اﻟﻤﺘﻤﯿﺰﯾﻦ وﻏﯿﺮھﻢ )ﺑﺤﺚ ﻣﺴﺘﻞ ﻣﻦ رﺳﺎﻟﺔ ﻣﺎﺟﺴﺘﯿﺮ( (Journal of the College of Education for Women, 2019)
The diversity in the amount of information and sources of knowledge have made the student unable to control the amount of information only on a fraction of them, and there was a defect and clear to students in the strategies of encoding information, storage and often revolves this shortcoming on the issue is a significant lack of capacity on the academic achievement of many students because of the method or way in which the student in information processing and low academic skills necessary to use a specific strategy to encode and store information in memory and retrieval. The aim of this study is to identify the (Meta Memory components and its relationship in strategies of memory at students in the schools of the best and others). as to separate research procedures has adopted a researcher scale components beyond the memory (Herzog and Dixon 1988, ) be the scale of the seven components (strategy, mission, volume or ability, change, anxiety, achievement, center) and (108 paragraph) , and the researcher and the researcher has build scale strategies for remembering and consists of four types of strategies (recitations, organization, imagination, illustration verbal) and (40 paragraph) was applied measurements on a sample of students from fifth class science students are outstanding and ordinary consisted of (400 students) inasmuch (177) of the outstanding students, and (223) of normal students were selected in the manner of ordinary . After analyzing the data results indicated use of multiple regression analysis as follows: - Showed that there is a pool of achievement of Predicts components beyond that predicted making hear memory strategies to remember when the outstanding students, and prediction achievement and strategy at the Centre and the ordinary students. - Showed that there was a gathering of achievement and the strategy and the center of the Predicts components beyond that predicted in imagine memory strategies to remember when the outstanding students and Predict achievement and the capacity or the ability of the students of ordinary Showed that there was a gathering of achievement and the capacity or ability and strategic components of predicts beyond the memory of the predicted regulatory strategies to remember when the outstanding students and the ordinary together . - Showed that there is a pool of achievement and the strategy and the center of the predicts components beyond the memory of that predicted imagination strategies to remember when the outstanding students and predict achievement and capacity of the students or the ability of ordinary students. - Showed that there is a pool of achievement and the strategy and the center of the predicts components beyond the memory that predicted verbal explanation of the strategies to remember when the outstanding students and predict of achievement and strategy at the ordinary students.